Statin Modulation of Human T-Cell Proliferation, IL-1β and IL-17 Production, and IFN-γ T Cell Expression: Synergy with Conventional Immunosuppressive Agents - Jameel, Ashmal (Hindawi Publishing Corporation, 2013)
HMG-CoA reductase inhibitors (statins) have been demonstrated to be immunomodulatory for human immune-mediated disease and in experimental models. The aim of this study was to compare statin-mediated immunosuppressive effects on human T-cell responses in vitro with those of conventional immunosuppressives (dexamethasone, cyclosporin A (CsA), mycophenolate, and rapamycin). Statins (atorvastatin, lovastatin, and simvastatin) were investigated for their modulatory effects on human PBMC viability, cytokine profiles, and T-cell proliferation. At concentrations that inhibited anti-CD3/28-stimulated T-cell proliferation (P < 0.01), simvastatin significantly decreased intracellular CD4(+) T-cell expression of IFN-γ (P < 0.01) to levels similar to those induced by conventional immunosuppressives. Atorvastatin and lovastatin also decreased IFN-γ expression, although to a lesser degree (P < 0.05). All three statins reduced levels of IL-17 production (P < 0.01). However, in response to anti-CD3/28 stimulation, simvastatin significantly upregulated IL-1β production (P < 0.05). The profile of cytokines produced in response to anti-CD3/28 stimulation was similar when both atorvastatin and dexamethasone were added as compared with dexamethasone alone, suggesting that atorvastatin can synergise with dexamethasone with respect to immunomodulation of cytokines. This data supports the hypothesis of selective statin-mediated immunomodulatory effects on human immune cells.